2013
DOI: 10.1007/s13762-012-0158-z
|View full text |Cite
|
Sign up to set email alerts
|

Nickel removal from electroplating waste water using stand-alone and electrically assisted ion exchange processes

Abstract: Wastewater discharged from metal-finishing processes usually contains nickel, a hazardous substance that is used extensively in the surface finishing industry. In the present study, an acidic solution containing nickel was treated using strong acid cation exchange resin. A continuous lab-scale cation exchange arrangement permitting the assessment of electric current as an enhancement mechanism was designed and utilized at different flow rates successfully. Applying the electrical potential enhanced the nickel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The Electro coagulation process involves several chemical reactions and physicochemical phenomena, which result in decomposition. Usually there are three steps that occur in sequential ways, and they are [8]:…”
Section: The Theory Of Electro-coagulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Electro coagulation process involves several chemical reactions and physicochemical phenomena, which result in decomposition. Usually there are three steps that occur in sequential ways, and they are [8]:…”
Section: The Theory Of Electro-coagulationmentioning
confidence: 99%
“…The removal values were (93.5%, 98.5%, 97.5%, 99.55%) at (4, 6, 7, 8) pH, respectively. The highest removal was obtained at pH parameter equal to 8, at 120 minutes, and the reason is that the aluminum electrode dissolves in the solution when the electric current passes, forming aluminum ions in the solution, forming several compositions of aluminum compounds -hydroxyl at pH value range (4)(5)(6)(7)(8). The type of compound formed depends on the pH value, which helps to remove nickel ions by the method of electro-coagulation as mentioned in previous works [11].…”
Section: Effect Of Acidity Function (Ph)mentioning
confidence: 99%
“…For instance, the majority of Ni plating industries utilizes sulfuric acid solutions to perform acid pickling for surface activation [11,15]. Alternately, Ca is used in electroless Ni plating to precipitate the phosphite anion formed from the reaction of the hypophosphite reducing agent and NiSO4 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Pb heads the list of environmental threats because, even at extremely low concentrations, it has been shown to cause brain damage in children [5]. A number of techniques have been used to remove the metal ions from wastewater effluents; including chemical precipitation [6], ion exchange process [7][8][9][10][11][12][13][14][15][16][17], electrolytic methods [18][19][20], adsorption onto activated carbon [21,22], low cost adsorbents such as kaolin, bentonite, blast furnace slag and fly ash [23 ], ion imprinted polymer (IIP) [24][25][26], organic-based ligand precipitation [26], membrane and reverse osmosis processes [28]. The industrial utilization of these methods has been found to be limited, because of the high capital and operating costs and/or the ineffectiveness in meeting stringent effluent standards.…”
Section: Introductionmentioning
confidence: 99%